2018
DOI: 10.1152/ajpcell.00109.2018
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective autophagy reduces mitochondrial content during starvation in Caenorhabditis elegans

Abstract: Starvation significantly alters cellular physiology, and signs of aging have been reported to occur during starvation. Mitochondria are essential to the regulation of cellular energetics and aging. We sought to determine if mitochondria exhibit signs of aging during starvation and whether quality control mechanisms regulate mitochondrial physiology during starvation. We describe effects of starvation on mitochondria in the first and third larval stages of the nematode Caenorhabditis elegans. When starved, C. e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Disrupting either of these processes did not restore mtDNA copy number in daf-2 mutants ( Figure 4A,B ), nor did we observe increased germline apoptosis in daf-2 mutants ( Figure 4—figure supplement 1A,B ). Because mitochondrial degradation can occur in a PINK1/Parkin-independent manner ( Allen et al, 2013 ; Di Rita et al, 2018 ; Hibshman et al, 2018 ), we therefore also tested for a potential role of mitochondrial fission, a common precursor of mitophagy, using a deletion in the gene drp-1 , which encodes a dynamin-related protein important for mitochondrial fission. Although we observed an increase in mtDNA copy number when mitochondrial fission is disrupted in animals with intact insulin signaling ( Figure 4C ), consistent with reduced mitophagy, we did not observe a rescue of mtDNA copy number in daf-2 These data suggest that the suppression of mtDNA content upon loss of insulin signaling is not mediated through the elimination of mitochondria by PINK/Parkin-dependent mitophagy, mitochondrial fission, or apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Disrupting either of these processes did not restore mtDNA copy number in daf-2 mutants ( Figure 4A,B ), nor did we observe increased germline apoptosis in daf-2 mutants ( Figure 4—figure supplement 1A,B ). Because mitochondrial degradation can occur in a PINK1/Parkin-independent manner ( Allen et al, 2013 ; Di Rita et al, 2018 ; Hibshman et al, 2018 ), we therefore also tested for a potential role of mitochondrial fission, a common precursor of mitophagy, using a deletion in the gene drp-1 , which encodes a dynamin-related protein important for mitochondrial fission. Although we observed an increase in mtDNA copy number when mitochondrial fission is disrupted in animals with intact insulin signaling ( Figure 4C ), consistent with reduced mitophagy, we did not observe a rescue of mtDNA copy number in daf-2 These data suggest that the suppression of mtDNA content upon loss of insulin signaling is not mediated through the elimination of mitochondria by PINK/Parkin-dependent mitophagy, mitochondrial fission, or apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria are dynamic organelles that change their network morphology, balancing their fission with fusion to maximise energy production [ 8 , 39 , 41 ]. In worms their morphology has been shown to change in response to starvation [ 42 ] as well as various DR protocols [ 39 , 43 ], and can be used to provide clues about an animal’s physiological state. In addition skn-1 has previously been implicated in the maintenance of muscle mitochondrial networks, and anoxia-induced mitochondrial dynamics, raising the question of whether these phenomena might be mediated by skn-1b [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the cellular level, starvation induces both mitochondrial and ER stress 53,80,84 . Mitochondria become fragmented in starved animals and are cleared through mitophagy 10,80,85 . Zhang et al 86 reported that starvation caused ER stress and led to activation of PERK/eIF2α in an astrocyte cell line.…”
Section: Discussionmentioning
confidence: 99%